2022
DOI: 10.1186/s12936-022-04379-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of healthcare providers to malaria case management guidelines of the formal private sector in north-western Ethiopia: an implication for malaria control and elimination

Abstract: Background Malaria is an infectious disease which has been globally targeted for elimination in at least 35 of 90 endemic countries by 2030. Most successful malaria elimination country programmes have engaged the private health sector in an effort to identify, document, investigate, provide effective treatment, and follow-up cases. However, there has been limited rigorous research showing evidence of adherence among healthcare providers of the formal private health sector to national malaria di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This finding is in consonance with other report. [18][19][20] The key informants consistently attributed this practice to shortage of clinical and laboratory personnel as well as inadequate testing materials in their health facilities. Shortage of man power and poor funding have been identified as major factors that hinder malaria policy implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in consonance with other report. [18][19][20] The key informants consistently attributed this practice to shortage of clinical and laboratory personnel as well as inadequate testing materials in their health facilities. Shortage of man power and poor funding have been identified as major factors that hinder malaria policy implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Presumptive treatment for uncomplicated malaria was also reported to be widely practiced among private health care providers in another survey. 19 Furthermore, another recent study in Eastern Uganda reveals that only about 50% of health care workers carry out case management of malaria in line with the WHO recommendations. 20 Unnecessary use of injectable drugs may amount to over treatment and is a form of drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in several sub-Saharan African countries have shown that private health facilities and drug outlet providers lack knowledge and do not adhere to national malaria case management guidelines [7][8][9][10][11][12]. This was confirmed by recent meta-analyses that reported healthcare provider reliance on clinical malaria diagnosis and low adherence to appropriate malaria case management guidelines [13][14][15].…”
Section: Introductionmentioning
confidence: 91%
“…Studies in several sub-Saharan African countries have shown that private health facilities and drug outlet providers lack knowledge and do not adhere to national malaria case management guidelines [7][8][9][10][11][12]. This was con rmed by recent meta-analyses that reported healthcare provider reliance on clinical malaria diagnosis and low adherence to appropriate malaria case management guidelines [13][14][15].…”
mentioning
confidence: 99%